Behavioral analysis of loan decision-making and influencing factors among food-producing new agricultural operating entities in China - Jingzhou Wei; Taihuang Fang (Frontiers in Sustainable Food Systems)
The inherent fragility of the agricultural industry significantly restricts the financing channels available to new agricultural operating entities. Access to credit loans emerges as a pivotal means to address capital shortages among farmers and enhance production inputs. Drawing on survey data from 17,745 new agricultural operating entities engaged in food production in Lu’an City, Anhui Province, and agricultural households documented in the China Household Finance Survey Database, this paper employs the Logit model and the Heckman selection model to empirically analyze the loan decision-making behavior of these entities from two perspectives: loan willingness and credit scale. The research reveals that several key variables exert a significant positive influence on the borrowing willingness of grain producers. Specifically, the planting area range, input range per hectare, the rate range of return on investment, membership in cooperatives, and operation as a family farm all notably enhance their willingness to seek loans. Conversely, the net income per hectare and the number of crop types cultivated significantly diminish their inclination to borrow. Additionally, male operators and those with higher educational backgrounds demonstrate a stronger willingness to obtain loans. Furthermore, the study indicates that the planting area and membership in cooperatives also positively correlate with the scale of loans secured by these agricultural operating entities. Therefore, from the perspective of food security, it is essential to cultivate food-producing new agricultural operating entities. This requires a focus on the counter-cyclical adjustment of financial support, increasing credit support during years of low investment returns. Additionally, it is necessary to develop multiple forms of moderate-scale operations, enhance policy support, and boost the production enthusiasm of food-producing new agricultural operating entities.